2019
DOI: 10.1007/s00431-019-03358-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring situation awareness and team effectiveness in pediatric acute care by using the situation global assessment technique

Abstract: Situation awareness (SA) is an important human factor and necessary for effective teamwork and patient safety. Human patient simulation (HPS) with video feedback allows for a safe environment where health care professionals can develop both technical and teamwork skills. It is, however, very difficult to observe and measure SA directly. The Situation Global Assessment Technique (SAGAT) was developed by Endsley to measure SA during real-time simulation. Our objective was to measure SA among team members during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
0
29
1
1
Order By: Relevance
“…In our study, we observed a relationship between SA and the students' technical skills, including achieving the goals of the scenario. In contrast to our results, similar pediatric simulations have shown no relationship between SA as assessed by the SAGAT method and achievement of the goal of the scenario [24]. In another study, this skill correlated with the team's clinical performance but did not correlate with the team's perception of shared understanding, team leader effectiveness, or team experience-similar to our results [25].…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, we observed a relationship between SA and the students' technical skills, including achieving the goals of the scenario. In contrast to our results, similar pediatric simulations have shown no relationship between SA as assessed by the SAGAT method and achievement of the goal of the scenario [24]. In another study, this skill correlated with the team's clinical performance but did not correlate with the team's perception of shared understanding, team leader effectiveness, or team experience-similar to our results [25].…”
Section: Discussioncontrasting
confidence: 56%
“…Although the exact methods for assessing SA in teams varied among these studies, a few general statements can be made. Shared SA as measured by SAGAT was shown to be predictive of overall team performance (Bonney, Davis-Sramek, & Cadotte, 2016;Coolen, Draaisma, & Loeffen, 2019;Rosenman et al, 2018), as well as when it was measured by SPAM (Cooke, Kiekel, & Helm, 2001). Combining SA scores into an overall Team SA score generated mixed results, with five studies showing it to be predictive of overall team performance (Cooke et al, 2001;Crozier et al, 2015;Gardner, Kosemund, & Martinez, 2017;Parush et al, 2017;Prince, Ellis, Brannick, & Salas, 2007), and three that did not (Brooks, Switzer, & Gugerty, 2003;P.…”
Section: Team Samentioning
confidence: 96%
“…greater capacity to regularly reassess patient's condition and situation, resulted in a higher score on the technical skills scale. In similar conditions of pediatric simulations no direct relationship was found between situation awareness and goal achievement [14]. In that study, consensus on the primary problem (shared mental model) led to faster achievement of predefined goals.…”
Section: Discussionmentioning
confidence: 71%